Grouping of handwritten Bangla basic characters, numerals and vowel modifiers for multilayer classification - Reza, Khondker Nayef; Khan, Mumit (© 2012 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the International Conference on Frontiers in Handwriting Recognition, ICFHR 2012; Bari; Italy; 18 September 2012 through 20 September 2012 [© 2012 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICFHR.2012.206